The acceptability and feasibility of an internet-administered, guided, low-intensity cognitive behavioural therapy intervention for parents of children treated for cancer: findings from a qualitative study involving public contributors ... - Thiblin, Ella; Lundgren, Johan; Bergqvist, Mattias; Huynh, Tho; Reuther, Christina; Rösler, Sandra; Woodford, Joanne; von Essen, Louise (figshare, 2025)
Abstract Background Despite parents of children treated for cancer commonly reporting psychological difficulties such as symptoms of depression and anxiety, there is a lack of evidence-based psychological interventions tailored to their needs. We therefore developed an internet-administered, guided, low-intensity cognitive behavioural therapy-based self-help intervention (EJDeR). We examined the acceptability and feasibility of the intervention and study procedures in the single-arm feasibility trial ENGAGE. Results suggested the intervention and study procedures are feasible and acceptable. However, a need for modifications and refinements to the intervention and study procedures was identified. We conducted a qualitative interview study to explore the acceptability and feasibility of the intervention and study procedures from the perspective of parents to inform modifications and refinements to the intervention and study procedures. Methods Semi-structured interviews were conducted with 52 parents (17 ...